Dominica : Seventh Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Financing Assurances Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Seventh Review Under the Poverty Reduction and Growth Facility (PRGF) for Dominica. Policy implementation under the program has remained strong. All end-June 2006 performance criteria were met, and all indicative targets for end-June and end-September were met with comfortable margins. Progress has been made on the structural benchmarks for the Seventh Review. Fiscal performance in FY2005/06 was commendably strong, and the FY2006/07 budget reflects a continuation of strong fiscal policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet